Use of isotopic and elemental fingerprints for seahorse species discrimination and traceability of geographic origin - Cabral, Ana Elisa; Calado, Ricardo; Palma, Jorge; Ricardo, Fernando; Ferreira da Silva, Eduardo; Patinha, Carla; Planas, Miquel (Frontiers in Marine Science, 2024)
Seahorses (Hippocampus spp.; Family Syngnathidae) are mainly targeted by Traditional Chinese Medicine, curio and ornamental trade, as dried or live specimens. Traceability tools may help fill the gaps on supply chains, securing information on geographic origin and identification of traded specimens. Fin-clipping, a non-lethal and well-established method in seahorse research, offers a potential approach to trace the geographic origin and certify the aquaculture of these flagship species. As such, this study aimed to investigate the existence of differences in isotopic profiles of four seahorse species cultured at research centers located in southern Portugal and northern Spain, as well as between cultured Hippocampus guttulatus sourced from two research centers, and between wild and cultured specimens of this species. This research also evaluated the potential of combining isotopic and elemental fingerprints for seahorse species discrimination, through inductively continuous-flow isotope ratio mass spectrometry (IR-MS) and plasma mass spectrometry (ICP-MS). Species cultured at the same research centers exhibited similar stable isotope composition (δ13C and δ15N), except in the case of temperate H. guttulatus from northern Spain, which differed significantly from tropical species H. kuda and H. reidi. These differences could be due to phylogenetic dissimilarities and differences in seawater temperature. The δ15N composition allowed to discriminate between cultured H. guttulatus from the two research centers and between cultured and wild specimens. While dorsal fin isotopes alone did not prove to be a reliable tool for the discrimination of different cultured species, combining them with elemental profiles from seahorses’ whole-body allowed to successfully discriminate between H. kuda and H. reidi. This preliminary research demonstrates the potential of stable isotope and elemental analyses for tracing seahorses’ geographic origin and species identification. However, further research should be performed to validate these findings for wild specimens, particularly those from illegal, unreported and unregulated (IUU) fisheries and trade.